Accounting Education and Its Place in the Romanian Economic Education Literature - Ileana Cosmina Pitulice; Lidia Cristina Manea (Journal of Accounting and Management Information Systems (JAMIS), 2015)
This article aims to review the economic education literature in Romania for the period 2011-2013, focusing on finding the accounting related topics. For the purpose of the analysis, the 99 articles are categorized in four main sections that are divided by subsections. Over the reviewed period, more than 160 authors contributed to the enrichment of economic education literature in Romania, publishing their papers in journals indexed in databases journals. The analysis revealed a predominance of papers debating the teaching methods, both traditional and modern (including E-learning), Romanian researchers being preoccupied of improving the teaching process in order to achieve the best quality for academic services. However, the research revealed a scarcity of accounting education topics while management information systems education is better represented.
Keywords: A22; A23; 650; higher education; journals; quality management; teaching process